Innovative principles of pedagogical training of medical universities lectures - Aleksey V. Kozlov; Sergey P. Potanin (Moscow Polytechnic University, 2022)
The organizational and methodological conditions are touched upon in the article as well as the problems in pedagogical training of entry-level lectures at medical universities. Also this article offers a new interpretation of andragogical principles of education, presents some advantages and disadvantages of concentrated organization of educational process and views the peculiarities in a usage of innovative didactics.